Crucial role of solid body temperature on elastohydrodynamic film thickness and traction. (March 2019) - Liu, H.C.; Zhang, B.B.; Bader, N.; Guo, F.; Poll, G.; Yang, P.
Abstract: The effect of the solid body temperature effect on film thickness and traction in elastohydrodynamic lubrication (EHL) has been studied numerically. At a moderate entrainment velocity, the EHL film behavior is controlled by the solid body temperature as the oil heats up to the body temperature before entering the contact zone and thus the film thickness decreases. For high velocity conditions, inlet shear and compressive heating also contribute to the reduction of film thickness. The results indicate that the measured film thickness and traction on disc machines might be lower than the expected values when the disc temperature exceeds the supplied oil temperature. Highlights: Solid body temperature effect ( T s o l i d ≥ T o i l ) exists in traction tests with disc machines. A quantitative thermal EHL model was built to analyze this effect. Solid body temperature affects the EHL film temperature and film thickness significantly. Simple film thickness prediction method with body temperature effect is given. For extremely high speeds, inlet shear and compressive heating were discussed.